The Diffusive Cynicism as a Sociocultural Antisystem - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The sociocultural construction of the modern world is based on the ideologies of the project of modernity, which are undergoing a crisis today. As in the whole world, so in the Armenian society, skeptical and cynical attitudes are being spread in relation to these ideologies. But in the Armenian society and in modernized societies the socio-cultural preconditions for the diffusion of cynicism in relation to ideologies are different. While in modernized societies the spread of cynicism is conditioned by the sociocultural preconditions of the consumer society, the formation of a postmodern culture and individualization, in Armenian society this is conditioned of the incompatibility of the sociocultural values and norms of the Armenian sociocultural environment and the ideologies of modernity. But in both cases, cynical societies are sociocultural antisystems for any ideologies.